Pharmacometric approaches to optimize use of drugs and dialysis treatments in patients with chronic kidney disease - Pfister, Marc (Henry Stewart Talks, 2014)
The therapeutic window, The emerging discipline of pharmacometrics, Challenges of studies in CKD patients, Pharmacometrics approaches in sexagliptin treatment, Pharmacometrics approaches in entecavir treatment, Individual bayesian kinetic modeling (IBKM), IBKM in adults, IBKM in pediatrics